2013
DOI: 10.1159/000350271
|View full text |Cite
|
Sign up to set email alerts
|

Second-Trimester Screening for Trisomy-21 Using Prefrontal Space Ratio

Abstract: Objective: To investigate the potential value of prefrontal space ratio (PFSR) in second-trimester screening for trisomy-21. Methods: A retrospective study utilizing stored midsagittal two-dimensional images of fetal profiles in 240 euploid and 45 trisomy-21 pregnancies at 16+0-23+6 weeks' gestation. The vertical distance between the leading edge of the skull and that of the skin (D1) and the distance between the skull and the mandibulo-maxillary line (D2) were measured and the D1:D2 rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 10 publications
5
16
1
Order By: Relevance
“…Previous sonographic studies have demonstrated that second‐ and third‐trimester fetuses with trisomy 21 show signs of mid‐facial hypoplasia, which can be assessed by measuring NB length, PT and PFSR. Our results suggest that a contribution to the flat face of fetuses with trisomy 21 is also provided by a shorter sphenofrontal distance, which could be due to dorsal displacement of the lower portion of the frontal bone (Figure ).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous sonographic studies have demonstrated that second‐ and third‐trimester fetuses with trisomy 21 show signs of mid‐facial hypoplasia, which can be assessed by measuring NB length, PT and PFSR. Our results suggest that a contribution to the flat face of fetuses with trisomy 21 is also provided by a shorter sphenofrontal distance, which could be due to dorsal displacement of the lower portion of the frontal bone (Figure ).…”
Section: Discussionsupporting
confidence: 51%
“…Ultrasound examination of the fetal profile in the second and third trimesters of pregnancy enables the assessment of several facial measurements that are significantly different in fetuses with trisomy 21 from in those that are chromosomally normal. Previous studies have shown that trisomy‐21 fetuses have an increased prevalence of nasal bone absence or hypoplasia, prenasal thickening, wide frontomaxillary facial angle, increased prenasal thickness (PT):nasal bone (NB) length ratio and high prefrontal space ratio (PFSR).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, which included 91 fetuses with trisomy 21, approximately 80% of the affected fetuses had a PFSR that was above the 95 th centile. Other study groups have confirmed these promising results.…”
Section: Introductionsupporting
confidence: 68%
“…The ratio is below the 5th percentile in about 80% of the fetuses with trisomy 21. Other workgroups have confirmed the good results using the PFSR …”
Section: Introductionmentioning
confidence: 57%